33.9k views
3 votes
Use basic trigonometric identities to simplify the expression: sin (-x) cos (-x) csc (-x) =?

User Augsteyer
by
5.8k points

2 Answers

2 votes

Hello!

The answer is:

The simplified expression is:


Sin(-x)*Cos(-x)*Csc(-x)=Cos(x)

Why?

To simplify the expression we need to use the following trigonometric identities:


Sin(-x)=-Sin(x)\\Cos(-x)=Cos(x)\\Csc(-x)=-Csc(x)\\Csc(x)=(1)/(Sin(x))

We are given the expression:


sin(-x)*cos(-x)*csc(-x)

So, applying the identities and simplifying, we have:


Sin(-x)*Cos(-x)*Csc(-x)=-Sin(x)*Cos(x)*-(1)/(Sin(x))


Sin(-x)*Cos(-x)*Csc(-x)=Cos(x)*-Sin(x)*-(1)/(Sin(x))


Sin(-x)*Cos(-x)*Csc(-x)=Cos(x)

Hence, the simplified expression is:


Sin(-x)*Cos(-x)*Csc(-x)=Cos(x)

Have a nice day!

User Jaeeun Lee
by
5.3k points
3 votes

Answer:


sin (-x) cos (-x) csc (-x) =cos(x)

Explanation:

We know by definition that the cosine is an even function, therefore


cos (-x) = cos (x)

We also know that the sin is an odd function, therefore


sin (-x) = -sin (x)

By definition:


cscx = (1)/(sinx).

Then:


csc(-x) = (1)/(sin(-x)).


csc(-x) = -(1)/(sin(x)).

Using these trigonometric properties we can simplify the expression


sin (-x) cos (-x) csc (-x)= -sin(x)cos(x)*(-(1)/(sin(x)))\\\\sin (-x) cos (-x) csc (-x)=cos(x)

User Macro
by
5.1k points